POSTGRADUATE CURRICULA IN ACCOUNTING. - Smith, C. Aubrey (The Accounting Review, 1948)
The topic assigned, that of discussing the graduate accounting curriculum from the viewpoint of schools offering undergraduate concentration in accounting, presents an opportunity to explore various phases of a most interesting and important subject. Prior to the twentieth century graduate work appeared to be limited to a high type of scholarship looking toward an intellectual career as opposed to a professional career. Accounting is universally recognized today as a profession ranking close if not on par with the older professional pursuits. The American Institute of Accountants has made extensive progress in preparing tests to ferret out those individuals with accounting aptitudes. Of late there has been developing some sentiment among some professors in some schools that the time put into writing a formal thesis could be better used in some other direction, such as additional courses or even field work. The MBA candidate should be required to pass a comprehensive test either written or oral or both. This examination to have any meaning and significance should be taken seriously by the examining committee as well as by the candidate.